Procedures for Resolving Banking Crimes within Islamic Financial Institutions: A Case Study of Financing Document Forgery in Murabahah Contracts - Roni Nasrulloh; Ramdani Wahyu Sururie; Oyo Sunaryo Mukhlas (Aghnina : Jurnal Hukum Ekonomi Syari'ah, 2026)
This study examines the procedures for resolving banking crimes within Islamic financial institutions, focusing on cases of document forgery in murabahah financing contracts. Murabahah dominates Islamic banking financing in Indonesia, making it particularly vulnerable to fraud arising from weaknesses in internal control, supervision, and document verification. This research aims to analyze the forms of document forgery in murabahah financing and to evaluate the mechanisms for resolving such crimes through internal institutional processes, non-litigation pathways, and litigation channels. Employing a qualitative approach with a case study design, the study utilizes primary data obtained through in-depth interviews with Islamic banking practitioners and law enforcement officials, alongside secondary data from legislation, court decisions, regulatory documents, and academic literature. The findings indicate that document forgery in murabahah financing commonly involves falsification of debtor identities, collateral documents, and transaction records. Resolution procedures generally prioritize internal settlement through audits, disciplinary sanctions, and recovery measures, followed by non-litigation mechanisms such as mediation and arbitration based on Islamic principles. Litigation is pursued when criminal elements are evident, involving both Religious Courts for civil disputes and General Courts for criminal prosecution. From both Islamic law and positive law perspectives, document forgery constitutes a serious violation of legal and ethical norms. The study highlights the importance of strengthening governance, compliance systems, and sharia supervision to prevent and effectively address banking crimes in Islamic financial institutions.